Design of ultrahigh refractive index metamaterials in the terahertz regime. (September 2017) - Jing, Xufeng; Xia, Rui; Gui, Xincui; Wang, Weimin; Tian, Ying; Zhu, Dongshuo; Shi, Guohua
Abstract: A high refractive index metamaterial was theoretically designed in the terahertz region, and the proposed structure is to easy implementation. By decreasing the diamagnetic effect with a thin "I"-shaped metallic patch structure and drastically increasing the effective permittivity through strong capacitive coupling in the unit cell, the higher refractive index of designed metamaterial can be obtained while maintaining low losses in the resonant frequency. The physical mechanism of metamaterial possessing an enhanced refractive index is revealed by the surface current, the electric field and magnetic field distributions. Besides, the polarization characteristics and broad incident angles robustness for the high refractive index are demonstrated. Highlights: A ultrahigh refractive index metamaterial was theoretically designed in the terahertz region. The physical mechanism is revealed by the surface current, the electric field and magnetic field distributions. The polarization characteristics and broad incident angles robustness are demonstrated.